The effectiveness of networking and collaboration in creative hubs: a case of Hub@Goethe - De Beer, Magdalena Gertruda (Rhodes University, Faculty of Commerce, Rhodes Business School)
This research took the form of a case study investigating the effectiveness of a single hub in South Africa, namely Hub@Goethe in Johannesburg. The context of the creative economy and creative industries provided insight into the experiences of creative cultural labourers in the new economic model. The context emphasised the research problem which considered the difficulties experienced by creative and cultural entrepreneurs and their career paths who, through labour precarity, remain isolated from the market, without access to physical spaces, network connections and business knowledge to realise their business ideas. The literature reviewed revealed how co-working office spaces, creative spaces and hubs provide creative entrepreneurs with the spatial infrastructure, amenities, and network access to mitigate challenges in the creative cultural sectors. These spaces offer a multitude of different amenities which is specific to their community's needs. Guided by the theory of social capital and structural holes reviewed in the literature, the effectiveness was assessed by the hub's ability to provide network access benefits or resource endowments. The research looked at whether the hub could provide creative cultural entrepreneurs with resource benefits such as a) access to social interactions, collaboration, and knowledge sharing, b) access to business or professional skills-based education programmes and mentorship, c) access to market and d) generation both social and economic benefit. The research adopted a qualitative approach, seeking insights into the creative entrepreneurs' experiences at the hub utilising one-to-one interviews. The thematic analysis confirmed that the hub was effective overall in providing entrepreneurs with access to benefits or resource endowments embedded in the network, confirming that hubs may be an effective tool in mitigating difficulties experienced by creative entrepreneurs in the creative industries. The research also showed areas of improvement where the hub could increase its experienced effectiveness, especially in reference to routes to market. The research findings inferred the importance of physical space, proximity and accessibility has on collaborative practices amongst creative entrepreneurs within the hub space.
Keywords: Cultural industries -- South Africa; Cultural industries Economic aspects -- South Africa; Economic development projects -- South Africa; Social entrepreneurship -- South Africa; Creative ability Economic aspects -- South Africa; Social capital (Sociology) -- South Africa; Social networks -- South Africa; Hub@Goethe